ANALISIS STRATEGI KAWASAN PENGEMBANGAN EKONOMI (KPE) BAGANSIAPIAPI DI PROVINSI RIAU - apriyanto, heri (Jurnal Sains dan Teknologi Indonesia, 2009)
Most of Country Border Area in Indonesia are underdeveloped area with limited social and economic infrastructure. On the adjacent area, the neighbor country such as Malaysia that adjacent with Sumatera already developed growth centersand border corridors with so many economic activities and trade. The disparity among country can not be avoided, mostly in economic aspect. To develop Country Border Area as equal with neighbor country and surrounding area, it is needed policy to establish Economic Development Area (KPE) in Country BorderArea. KPE is an area consist of some districts in border area that functionally bond to develop integrated superior economic. One of KPE developed is KPE Bagansiapiapi in Riau Province that adjacent with Malaysia. It has strategic location and abundant natural resources, but limited infrastructure as a constrainon economic development. For that reason, it is needed to formulate KPE Bagansiapiapi Strategic Plan based on agropolitan-marine integrated development area (AMIDA) concept.